Evaluation of cone beam computed tomography referral profile: Retrospective study in a Turkish paediatric subpopulation - GÜMRÜ TARÇIN, BİRSAY; TARÇIN, BİLGE; İDMAN, ENDER; GÜLDALI, MELİS (ARIESDUE SRL, 2021)
Aim Increasing use of cone beam computed tomography (CBCT) for dentomaxillofacial diagnosis raises concerns about radiation dose which is known to be higher compared to conventional dental imaging methods. This retrospective study investigated the CBCT referrals in a Turkish paediatric subpopulation in terms of referring department, field of view (FOV), and findings. Materials and methods A total of 8,880 CBCT images were reviewed retrospectively and images of paediatric patients (<= 14 years old) were selected. In paediatric patients; data related to patient age and gender, referring department, FOV, region of interest for localised applications, and reason for CBCT referral were recorded. FOVs of CBCT scans were classified as face, jaws (maxilla and mandible), maxilla, mandible, and tooth. CBCT indications were categorised based upon an adaptation of the European DIMITRA (dentomaxillofacial paediatric imaging: an investigation towards low-dose radiation induced risks) multicenter and multidisciplinary project recommendations as impacted teeth, trauma, orofacial clefts, dental anomalies, bone pathology, syndromes, and other. Patients undergoing consecutive CBCT examinations for follow-up were also recorded. In order to record the incidental findings noticed in the CBCT evaluation, the radiological report prepared by the radiologist was used. The results were analysed statistically with a significance level set at p<0.05. Results Four hundred forty-nine of the 8880 CBCT scans were taken from paediatric patients under the age of 14, representing approximately 5% of all scans. Most of the referrals were from Department of Paediatric Dentistry (36.3%), followed by Department of Orthodontics (25.6%). The most frequently imaged region was the maxilla (33.4%), followed by the face (20.5%). The most common region of interest for localised applications was the maxillary canine/incisor region (85.55%). The most common indication was impacted teeth (41.4%) followed by bone pathology (31%) and dental anomalies (29.6%); 11.6% of the patients underwent follow-up CBCT examinations especially for orofacial clefts and syndromes. Conclusions This retrospective study investigating CBCT indications in a Turkish paediatric subpopulation and comparing existing applications with DIMITRA project recommendations can guide dental professionals in referring paediatric patients for CBCT.
Keywords: Cone beam computed tomography; Paediatric population; Field of view; Indication; DIMITRA project guidelines